„…Hogy egyek legyenek, mint mi” – az egység kérdése - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
That they may be one, as we are” – the question of unity. 2019 is the Year of unity in the Hungarian Reformed Church since 10 years ago, when the Hungarian Reformed Churches on 22 May ex-pressed their unity by accepting a common constitution. In the era of Reformation, in the 16ᵗʰ century the young reformed church of the Hungarian territories was divided in three parts. The Western region was brought under the rule of the Habsburg Empire, in the Eastern territory the independent Principality of Transylvania emerged and the biggest “third” of the former kingdom, the part in the middle was conquered by the Ottomans. The first common organizational structure for the whole Hungarian Reformed Church was possible only in 19ᵗʰ century, following the Austro-Hungarian Compromise of 1867. The developing of the first constitution was finished in 1881, in Debrecen. After the two World Wars the Hungarian Reformed people lived not only in Hungary, but with a sudden political move they were citizens of Austria, Slovakia, Romania, Ukraine, Serbia, Croatia and Slovenia. In the latter century there have arisen significant Hungarian Re-formed communities also in distant lands, not only in the traditionally Hungarian region. The Consultative Convent prepared a common liturgy and hymnal beyond the harmonization of reformed church law, which is a considerable result for the songs are important factors of unity. The disgregation / fragmentation is an old problem of humanity and of Christianity. The alternative is the koinonia, the true communion with God and with fellows. This study has its purpose in seeking possibilities to realize unity between people, the fellows in Jesus Christ.